Predictive model for depressurization-induced blistering of type IV tank liners for hydrogen storage. (30th November 2017) - Yersak, Thomas A.; Baker, Daniel R.; Yanagisawa, Yuka; Slavik, Stefan; Immel, Rainer; Mack-Gardner, André; Herrmann, Michael; Cai, Mei
Abstract: The work described in this study represents the first effort to model the complex phenomenon of plastic liner blistering during the depressurization of type IV hydrogen storage tanks. Blistering occurs because gas is absorbed by the plastic liner at high pressure and stresses are generated when the decompression rate exceeds the rate by which absorbed gas can escape by diffusion. It is important to eliminate blistering because type IV tanks are the lightest hydrogen storage option for GM and Honda's first generation of fuel cell vehicles. This report details the implementation of a simple polymer liner blistering model which is based on Henry's law, Fick's 2nd law, and a simple material yield criterion derived from continuum mechanics. Since the model agreed well with experiment, a parametric study was conducted to predict the onset of blistering as a function of liner thickness and depressurization rate. The model sets the basis for a predictive tool for the pre-selection of liner materials and designs. The pre-selection approach reduces the number of experiments that need to be conducted which potentially reduces the cost of hydrogen storage system development. Highlights: A simple model was developed to predict blistering of Type IV tank liners. The blistering model uses Henry's law, Fick's 2nd law, and a yield criterion. Model predictions were validated qualitatively with experimental results. Parametric analyses of HDPE and PA liners are used to inform liner design.